Ritual, Resistance, and Rights: The Balia Healing Practice and Indigenous Policy Challenges in Palu, Indonesia - Pratiwi, Sulistya (Tashwirul Afkar, 2024)
Colonialism has caused environmental and social changes that harm indigenous peoples’ quality of life, traditional knowledge, and health. Regional policies govern Indonesian traditional knowledge protection. This study examines how acknowledging and maintaining traditional knowledge affects indigenous populations’ well-being, concentrating on the Balia ritual in Central Sulawesi’s Kaili indigenous community.The Kaili people, a nomadic agricultural group, have been marginalized and discriminated against by society and government. Historical legacy of the Kaili people includes the Balia ceremony, a traditional health and healing expertise. The practice fosters goodwill between the Kaili and Bugis and helps sick people recover. As a medicinal method, agricultural, and social activity, the Balia ceremony is part of Kaili culture. The Kaili believe that ceremonies involving supernatural nature affect soil fertility, weather, and pest control in agriculture. Traditional knowledge recognition and protection have proceeded slowly and inconsistently. Balia rites, a Kaili tradition, are becoming more popular due to their nomadic lifestyle and Gaia religion. After harvesting, the Kaili move to let the region regrow. Due to their link to the deity and trust in supernatural forces, Balia rituals are authentic despite cultural acculturation and a flourishing religion. Musical instruments and poetry phrases are used in illness rituals. The Kaili resist changing the practice and maintain public acceptability. Balia rites were questioned after the 2018 Palu, Sigi, and Donggala disasters, yet they continue to follow their ancestral beliefs. To defend indigenous people’s human rights, further research is needed on the Kaili people’s traditional health and healing expertise.